Idiopathic Pulmonary Fibrosis (IPF) incidence and prevalence in Italy - Agabiti, Nera; Porretta, Maria Assunta; Bauleo, Lisa; Coppola, Angelo; Sergiacomi, Gianluigi; Fusco, Armando; Cavalli, Francesco; Zappa, Maria Cristina; Vignarola, Rossana; Carlone, Stefano; Facchini, Gianpiero; Mariotta, Salvatore; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
Background: Studies of Idiopathic Pulmonary Fibrosis (IPF) epidemiology show regional variations of incidence and prevalence; no epidemiological studies have been carried out in Italy. Objective: To determine incidence and prevalence rates of IPF in the population of a large Italian region. Methods: in this cross-sectional study study data were collected on all patients of 18 years of age and older admitted as primary or secondary idiopathic fibrosing alveolitis (ICD9-CM 516.3) to Lazio hospitals, from 1/1/2005 to 31/12/2009, using regional hospital discharge, population and cause of death databases. Reporting accuracy was assessed on a random sample of hospital charts carrying the ICD9-CM 516.3, 516.8, 516.9 and 515 codes, by reviewing radiology and pathology findings to define cases as IPF “confident”, “possible” or “inconsistent”. Results: Annual prevalence and incidence of IPF were estimated at 25.6 per 100,000 and 7.5 per 100,000 using the ICD9-CM code 516.3 without chart audit while they were estimated at 31.6 per 100,000 and at 9,3 per 100,000 for the IPF “confident” definition after hospital chart audit. Conclusion: The data provide a first estimate of IPF incidence in Italy and indicate that incidence and prevalence in southern European regions may be similar to those observed in northern Europe and North America.